A framework for procurement process re-engineering in Industry 4.0. Issue 2 (24th December 2020) - Tripathi, Shubham; Gupta, Manish
Abstract : Purpose: Procurement is a crucial part of supply chain management, consistently becoming a strategic vantage point in global competition. The industry 4.0 paradigm is transforming supply chains to smarter systems, giving rise to the concept of procurement 4.0. A systematic framework to transform in current scenario is crucial. Design/methodology/approach: This study brings together these current researches to propose a redesigned procurement process by combining several technologies. A BPR approach is taken to present the new process and its merits are discussed. Findings: A re-designed procurement framework is proposed. Radical improvements of cost, cycle time, human effort, degree of automation, traceability, information availability and uncertainty are achievable with the proposed framework. Practical implications: The proposed re-engineered process addresses the visualization barrier for managers. The proposed framework is grounded on BPR which provides a generic ground for developing redesign exercise along with the visualization of new process. Originality/value: There is literature discussing implementation, impact and advantages of individual and combination of technologies on procurement process but lacks visualization of the transformed process combining these technologies.